Implementation of fuzzy analytical hierarchy process (FAHP) and TOPSIS for scholarship decision support system for the underprivable - Kurnia, Fitra; Amri, M Khairul (Science, Technology, and Communication Journal, 2026)
Scholarship is part of assistance given by organization, company, institution or person. One of the existing scholarships at SMKN 2 Bengkalis is underprivileged scholarship given to students with middle to lower economic levels. This research does for helping underprivileged scholarship selectors in SMKN 2 Bengkalis to choose who are recommended eligible students as recipients of underprivileged scholarships with set established criteria before. Fuzzy analytical hierarchy process method implemented in this research with 7. With several criteria having each 4 – 5 values. And this research uses 239 active students data in SMKN 2 Bengkalis in 2021 as a decision alternative. Testing is done with 2 methods that are black box which system has worked in accordance with expected and UAT by 79% of both respondents. After obtaining the preference value, the final results of the ranking are obtained, the order of the smallest value of the student who is most. Entitled to receive scholarship assistance, namely students 1, 5, and 10.